Interface engineering of NiTe@CoFe LDH for highly efficient overall water-splitting. (5th September 2022) - Yao, Linchao; Li, Rong; Zhang, Huaming; Humayun, Muhammad; Xu, Xuefei; Fu, Yanjun; Nikiforov, Anton; Wang, Chundong
Abstract: Design and synthesis of highly active, inexpensive and durable catalyst for simultaneous hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is highly desired for green hydrogen generation. In this work, high conductivity NiTe nanorods are coupled with amorphous CoFe layered double hydroxide (LDH) to achieve a hierarchical NiTe@CoFe LDH heterostructure via a hydrothermal reaction and a subsequent electrodeposition process. The as-prepared three-dimensional (3D) self-supported NiTe@CoFe LDH nanorods endow highly efficient electron transfer and mass diffusion, and this architecture with abundant electrode/electrolyte interfaces can provide more active sites. Consequently, with the synergistic effect of NiTe and CoFe LDH, the as-prepared NiTe@CoFe LDH electrocatalyst achieved a current density of 10 mA cm −2 with low overpotentials of 218 mV and 103 mV for OER and HER, respectively, and showing a robust stability for 50 h. Furthermore, an alkaline electrolyzer with NiTe@CoFe LDH serving as both the anode and cathode requires a cell voltage of 1.56 V to yield 10 mA cm −2 current density, and can sustain for more than 50 h, with a slightly current density increase of 5%, showing potential for practical industrial application to generate hydrogen. This work highlights the construction low cost highly efficient 3D rods electrode for promising applications in green hydrogen generation. Highlights: Novel hierarchical NiTe@CoFe LDH heterostructure electrocatalyst are fabricated. 3D structure benefits electrolyte diffusion and gas releasing. Prepared catalyst only require 262 mV and 103 mV to drive 100 mA cm −2 for OER and 10 mA cm −2 for HER, respectively. NiTe@CoFe LDH delivers a cell voltage of 1.56 V for overall water splitting.